Marketing Plan For Recycled Paper Hub Business Project - Pratama, Aditya; Indradewa, Rhian; Yanuar Rahmat Syah, Tantri; Kustiawan, Unggul (Dinasti Publisher, 2024)
Businesses that run in recycling industries are one of the trends that are now in demand by many parties and supported by both national and international governments, but in the practice of these business activities there are many components that must be considered, especially if an entity is in the business to business sector. PT Recycled Paper Hub came as an competitive alternative that offers products in the form of recycled paper materials with low impurity levels which will later be used by companies to be processed again into many forms including packaging. By analyzing and implementing a marketing mix approach in accordance with the vision and mission, analysis data obtained from research on internal and external strengths that are quantitative and qualitative, the data obtained reflects business activities in order to achieve business excellence. In this study, the marketing mix carried by PT Recycled Paper Hub is Direct Marketing NICE.